4(5x+25)
5(4x+20)
10(2x+10)
2(10x+50)
20(x+5)
hope this helps
Check the picture below, so let's check the equations below hmmm
![\boxed{A}\\\\ y=\cfrac{16-3x}{4}\implies y=\cfrac{-3x+16}{4}\implies y = \cfrac{-3x}{4}+\cfrac{16}{4}\implies y=-\cfrac{3}{4}x\stackrel{\stackrel{b}{\downarrow }}{+4}~\hfill \bigotimes \\\\[-0.35em] ~\dotfill](https://tex.z-dn.net/?f=%5Cboxed%7BA%7D%5C%5C%5C%5C%20y%3D%5Ccfrac%7B16-3x%7D%7B4%7D%5Cimplies%20y%3D%5Ccfrac%7B-3x%2B16%7D%7B4%7D%5Cimplies%20y%20%3D%20%5Ccfrac%7B-3x%7D%7B4%7D%2B%5Ccfrac%7B16%7D%7B4%7D%5Cimplies%20y%3D-%5Ccfrac%7B3%7D%7B4%7Dx%5Cstackrel%7B%5Cstackrel%7Bb%7D%7B%5Cdownarrow%20%7D%7D%7B%2B4%7D~%5Chfill%20%5Cbigotimes%20%5C%5C%5C%5C%5B-0.35em%5D%20~%5Cdotfill)

Answer:
a=(-3.2)
Step-by-step explanation:
a+(-1.3)=(-4.5)=a-1.3=(-4.5)
a=(-3.2)
Please mark as Brainliest! :)
Have a nice day.